Made by humans - Broad, Ellen (Melbourne University Press, 2018)
AI can be all too human quick to judge, capable of error, vulnerable to bias. It's made by humans after all. Humans design the systems and tools that make new forms of AI faster. Humans are the data sources that make AI smarter. Humans will make decisions about how to use AI. The laws and standards, the tools, the ethics. Who benefits. Who gets hurt. "Made by Humans" explores our role in automation and the responsibilities we must take on.